Bone Graft Augmentation for Severe Glenoid Bone Loss in Primary Reverse Total Shoulder Arthroplasty: Outcomes and Evaluation of Host Bone Contact by 2D-3D Image Registration. Issue 3 (28th September 2017) - Lorenzetti, Adam; Streit, Jonathan J.; Cabezas, Andres F.; Christmas, Kaitlyn N.; LaMartina, Joey; Simon, Peter; Frankle, Mark A.
Abstract : Background: The treatment of patients with severe glenoid bone loss using reverse total shoulder arthroplasty (RSA) is challenging because of the difficulty in obtaining glenoid fixation. The outcomes following primary RSA with structural bone-grafting for severe glenoid bone loss and the amount of native bone support necessary to achieve clinical improvement are unclear. Methods: We reviewed functional outcomes (American Shoulder and Elbow Surgeons [ASES] score, Simple Shoulder Test [SST], visual analog scale [VAS] for pain and function, patient satisfaction, and range of motion) for 57 patients who were treated with a primary RSA and glenoid bone-grafting for severe glenoid bone loss. Three glenoids were classified as type A2; 2, as type B2; and 2, as type C, according to the Walch classification; 16 glenoids, as grade E1; and 19, as grade E3, according to the Sirveaux classification; 9 glenoids, as grade 3, according to the Levigne classification; and 6 were unable to be classified. For the 44 patients with adequate preoperative computed tomographic (CT) data and postoperative radiographs, we evaluated native bone contact under the glenoid baseplate by matching the projected shape of the implant and scapula from the postoperative radiographs with a generated 3-dimensional (3D) model of the preoperative scapula. We then analyzed functional outcomes in relation to native bone support of the baseplate. Results: At a mean of 46 months (minimum, 24 months), the patients demonstrated significant improvements in function, motion, and pain (change in the ASES total score = 38.6, change in SST = 5.4, change in forward elevation = 72.4°, change in abduction = 67.7°, change in external rotation = 24.3°, and change in VAS pain score = −4.6; p < 0.001 for all). On the basis of the generated 3D model, the baseplate contact to host bone was a mean (and standard deviation) of 17% ± 12% (range, 0% to 50%). There was no significant correlation between host bone coverage and change in the ASES score (p = 0.51) for the 44 patients included in this analysis. There were 4 major complications (7%) in the study group but no glenoid baseplate failures. Conclusions: Glenoid bone-grafting in a primary RSA in a shoulder with severe bone loss produces good functional outcomes that do not correlate with the degree of native bone contact under the baseplate. We had observed no glenoid component failures at the time of writing. Level of Evidence: TherapeuticLevel IV . See Instructions for Authors for a complete description of levels of evidence.